Two-dimensional electron momentum spectra of argon ionized by short intense lasers: Comparison of theory with experiment - Morishita, Toru; Chen, Zhangjin; Watanabe, Shinichi; Lin, C. D. (My University, 2007)
We studied the two-dimensional electron momentum spectra of Ar by femtosecond intense laser pulses with mean wavelength from 400nmto800nm, to compare with experimental results of Maharjan et al. [J. Phys. B 39, 1955 (2006)]. At the higher intensities we found that the effects of ground-state depletion and laser-focus volume are very important such that the peak laser field strength is not reached in experiment. The ubiquitous fanlike stripes in the low-energy electron momentum spectra and the evidence of Freeman resonances in the experimental data are well reproduced in the theoretical calculations. We emphasize that depletion of the initial state should be carefully evaluated for ionization of atoms in the tunneling region.